Essential Characteristics Of A Successful Construction Project Manager In The Malaysian Construction Industry - Chang, Khong Thong (2019)
The construction industry is an important industry in any country in the world, more so in the developing countries. While it may contribute a relatively small percentage to the Gross Domestic Product in any country as compared to the other major industry like the mining or agricultural industries, its importance lie in the fact that due to its nature, the construction industry is directly link to a long list of supply chain industries and therefore have a hugh multiplier effects to the country’s overall economy. In a developing country like Malaysia, the annual spending on the physical infrastructural development aspect of the country occupies a significant percentage of the country’s annual budget. Having a poor project management team in implementing these hugh projects would mean that billions of tax payers money would be wasted unnecessarily. It is therefore imperative that an effective project management team be deployed for these hugh projects. It is therefore the aim of this study to evaluate on the essential characteristics that a successful construction project manager should possess in the Malaysian construction industry. They survey data was collected from fifty four respondents out of a total of about three hundreds survey questionnaire emailed to the relevant and selected industry practitioners. The data collected was then evaluated by statistical method using Microsoft Office Excel and SPSS (Statistical Package for the Social Science) where appropriate to produce a ranking of a list of essential characteristics for a successful construction project manager in the Malaysian construction industry. The top ten essential characteristics are: critical analysis and judgement; leadership qualities; strategic perspective; determination on objective; engaging communication and feedback; conflict management; resource management abilities; vision and imagination of impact of action taken; trustworthiness and verbal skill. This study have resulted in a useful list of essential characteristics for a successful construction project managers that is relevant to the Malaysian construction industry. This list of essential characteristics can be utilise as a reference point for the future soft skill training of prospective construction project manager both in the tertiary vii educational programme as well as upgrading of soft skill training for junior construction project manager. It is hope that this will in turn lead to more effective and efficient management of our Malaysian governmental infrastructural development projects and thus minimise the wastage of billions of tax payer’s money. On a broader perspective, these will also hopefully lead to better efficiency in the overall management of the country resources in term of managing construction projects.